Analisis Pengaruh Storytelling Marketing Terhadap Kinerja Pemasaran Melalui Brand Image: (Studi pada STKIP Modern Ngawi) - Pamula, Mahardhika (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
The increasingly fierce competition between universities demands that higher education institutions adopt marketing strategies that are not only informative but also able to build emotional attachment and positive perceptions in the minds of prospective students. One relevant approach is storytelling marketing, which conveys marketing messages through meaningful and authentic narratives. This study aims to analyze the effect of storytelling marketing on marketing performance through brand image at STKIP Modern Ngawi. This study uses a quantitative approach with a survey method of 140 high school/vocational high school/Islamic high school students in Ngawi and Sragen Regencies, where each school is represented by one respondent. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS software. The results show that storytelling marketing has a positive and significant effect on brand image (CR = 6.649; p-value = 0.000). Furthermore, brand image has a positive and significant effect on marketing performance (CR = 3.675; p-value = 0.000). Furthermore, storytelling marketing also has a direct and significant impact on marketing performance (CR = 3.480; p-value = 0.001). This finding indicates that brand image plays a crucial role in strengthening the influence of storytelling marketing on marketing performance.